2019
DOI: 10.1097/qad.0000000000002060
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of visceral and subcutaneous adipose depots to markers of arterial injury and inflammation among individuals with HIV

Abstract: Objective: Persons living with HIV (PLWH) well-treated on antiretroviral therapies remain at risk for ensuing arterial disease. We investigated the relationship between adipose depots and biomarkers of arterial injury and inflammation to gain insight into the link between body composition and CVD risk.Designs/Methods: 155 HIV-infected and 70 non-HIV-infected individuals were wellphenotyped for body composition. Adipose depots were assessed via single-slice abdominal CT. Circulating markers of arterial disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…[26] Visceral fat is more metabolically active than subcutaneous fat [27] and affects the development of metabolic disturbances by contributing to the pro-inflammatory milieu (“meta-inflammation” [28] ). In previous studies, [25,29] increased VAT showed a significant relationship with systemic inflammation. In line with the former study, [29] this study also assessed the association between various markers of systemic inflammation and visceral obesity.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…[26] Visceral fat is more metabolically active than subcutaneous fat [27] and affects the development of metabolic disturbances by contributing to the pro-inflammatory milieu (“meta-inflammation” [28] ). In previous studies, [25,29] increased VAT showed a significant relationship with systemic inflammation. In line with the former study, [29] this study also assessed the association between various markers of systemic inflammation and visceral obesity.…”
Section: Discussionmentioning
confidence: 77%
“…In previous studies, [25,29] increased VAT showed a significant relationship with systemic inflammation. In line with the former study, [29] this study also assessed the association between various markers of systemic inflammation and visceral obesity.…”
Section: Discussionmentioning
confidence: 77%
“…Thus, investigating the impact of fat accumulation on immunomodulatory molecule is of primary importance. Adipose tissue distribution and its metabolic consequences have been widely studied in the context of HIV infection [1,6], but studies on adipose tissue-related immune functions, especially macrophage infiltration, are scarce and results contradicting [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…inflammation (11)(12)(13). Relative changes in adipose depots, ranging from the loss of SAT and/or accumulation of VAT, are associated with the development of dyslipidemia (14), insulin resistance (15), and increased markers of inflammation (13), which are key contributors to CVD (11)(12)(13)(16)(17)(18).…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…Composite risk for CVD in HIV may be inclusive of traditional and nontraditional risk factors , such as antiretroviral therapy (ART) use , inflammation, and immune activation . Relevant to this, PWH are predisposed to a unique fat redistribution clinically characterized by loss of subcutaneous (peripheral) adipose tissue (SAT) and/or accumulation of visceral adipose tissue (VAT), which may contribute to increased inflammation . Relative changes in adipose depots, ranging from the loss of SAT and/or accumulation of VAT, are associated with the development of dyslipidemia , insulin resistance , and increased markers of inflammation , which are key contributors to CVD .…”
Section: Introductionmentioning
confidence: 99%